Twitter as a right-wing populist's playground: The algorithmic populism of Dutch political party 'Forum voor Democratie' and leader Thierry Baudet during their political rise. (December 2021) - van Raalte, Anoek; Maeseele, Pieter; Phelan, Sean
Abstract: Dutch political party 'Forum voor Democratie' grew from a small party with two seats in the House of Representatives to becoming the largest party in the 2019 provincial elections. Since its creation in 2016, it has been accused of engaging in populist tactics, and has been labelled a far right party. This paper examines these claims by means of a qualitative Social Media – Critical Discourse Study of 250 tweets posted from March 2017 to March 2019 on the accounts of the party and its leader Thierry Baudet. Drawing on the concept of "algorithmic populism", we show that prototypical right-wing populist tropes such as othering, heartland, leadership, and conspiracy theorizing are all visible patterns in the Twitter discourse of both Baudet and the party. We conclude by discussing how these tropes are articulated more provocatively in Baudet's personal account, and the general significance of the media-conscious style of far right politics articulated by the party.